Marked variations in reproductive characteristics of snapper (Chrysophrys auratus, Sparidae) and their relationship with temperature over a wide latitudinal range - Wakefield, Corey; Potter, I.; Hall, N.; Lenanton, R.; Hesp, S. (Oxford University Press 2009, 2015)
© 2015 International Council for the Exploration of the Sea All rights reserved.The timing and duration of spawning and maturation schedules of Chrysophrys auratus were determined for populations in one subtropical (258S on the upper west coast) and two temperate regions (328S on the lowerwest and 358S on the south coasts) over .2000 km of coastline along the west coast of Australia. This study thus encompassed the wide latitudinal range of this recreationally and commercially important sparid in this region. The results were used, in conjunction with previously published data, to explore traditional paradigms regarding the relationships between the reproductive characteristics and variations in water temperature. Spawning at each latitude occurred mainly at 19-218C, but following a decline in temperature in the subtropical region and after a rise in temperature in the two temperate regions. Spawning on the upper west coast thus occurred between mid-Autumn and early spring (7 months) as opposed to late winter to early summer on the lower west coast (6 months). Spawning on the south coast was mainly restricted to mid-spring to early summer (2-3 months) in 2003 and 2004 and did not occur in 2005 whentemperatures in this periodwere the coldeston record. Thus, marked interannual differences in the prevalence of mature fish on the south coast probably reflect the "marginality" of the population. The length (L50) and age (A50) at which C. auratus matured increased markedly from 25 to 328S. Studies such as this allow for latitudinal variations in reproductive characteristics to be incorporated into population models to optimize fisheries sustainable yield, and contribute towards appropriate spatial scales for sustainable management strategies (e.g. minimum legal lengths consistent with latitudinal variation in length-based maturity schedules). The narrow temperature range over which this species spawns accounts for its current latitudinal distribution and enables predictions ofhowthis distribution might alter with climate change. This study provides relevant information for management and climate change implications for similar subtropical and temperate marine teleosts.